2020
DOI: 10.1186/s12992-020-00614-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable support solutions for community-based rehabilitation workers in refugee camps: piloting telehealth acceptability and implementation

Abstract: Background The lack of training and education of Community-Based Rehabilitation (CBR) workers poses one of the most significant barriers to receiving effective occupational, physical and speech therapy for individuals with disabilities in Low-to-Middle Income Countries (LMIC), especially in countries with significant refugee populations. The aim of this study was to successfully implement a telehealth support system for CBR workers, evaluate the feasibility and acceptability of this intervention’s implementati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…The details of the results related to the project design and implementation factors are as follows. Among the barriers, System usability issues were most cited (20)(21)(22)(23), especially in lower-level health facilities (23). Three studies researched and identified barriers related to internet access: Unavailable and unreliable or expensive Internet access (20,22,24).…”
Section: Project Design and Implementation Factors Levelmentioning
confidence: 99%
“…The details of the results related to the project design and implementation factors are as follows. Among the barriers, System usability issues were most cited (20)(21)(22)(23), especially in lower-level health facilities (23). Three studies researched and identified barriers related to internet access: Unavailable and unreliable or expensive Internet access (20,22,24).…”
Section: Project Design and Implementation Factors Levelmentioning
confidence: 99%
“…Current research suggests that in these settings, appropriate communication technology (which this manual seeks to support) can be used to: facilitate caregiver training, 3 support CBR workers, 2 build the individual person's competencies, performance, capacity and participation, 3 and even address inequitable access to quality health care. 2 The people who received remote services via the pilot manual and church volunteer support rated the process and outcomes surprisingly positive, given that these services are intended as a substitute or replacement for face-to-face services where they are unavailable or unaffordable. It was concluded that this is a suitable foundation for further expansion and refinement of the manual and these approaches.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…1 In LMIC, telehealth is increasingly identified as a potential support mechanism for intermediate level workers in rehabilitation and disability services, 2 and to support personal care in the home. 3 Indications are that telehealth approaches are beneficial to support Community Based Rehabilitation (CBR) workers who assist vulnerable and marginalized populations, 2 and when used consistently to guide workers, can improve outcomes for people with disabilities. 3…”
Section: Precedentmentioning
confidence: 99%
“…[35] found that using technology in treating patients is beneficial in terms of enabling the self-management, portability of treatment, and allowing the anonymous participation. Finally, in the term of acceptance and satisfaction toward the Tele-Health services, many researchers found that it is acceptable and satisfactory for both patients and clinicians Dynphy et al, 2017, [22], [33]), it could promote better levels of engagement with health care providers [34], and it could provide a solution for remote athlete patients during COVID-19 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another article used descriptive report of how to move from in-clinic to Tele-Health care during the COVID-19 pandemic [9]. A pilot study conducted in order to evaluate feasibility and acceptance of implementing Tele-Health by workers of Community-Based Rehabilitation [33]. Master class paper method was used in one article is [7].…”
Section: Grand Total 32mentioning
confidence: 99%